Penerapan Transparansi dan Akuntabilitas dalam Pengelolaan APBDes pada Desa Munte Kecamatan Likupang Barat - Kaaro, Resindi Elisabet; Morasa, Jenny; Sardjono, Olivia (Riset Akuntansi dan Portofolio Investasi, 2025)
Transparency and accountability are open to all. The results of services are fully accountable. The objective of this research is to ascertain how the principles of transparency and accountability are implemented in the management of the APBDes in Munte Village, West Likupang District, North Minahasa Regency. This research used a qualitative approach and descriptive analysis as the analytical method. The research findings are clear: the implementation of transparency and accountability in APBDes management in Munte village, West Likupang subdistrict, has partially gone well. The management of the village income and expenditure budget is in accordance with Permendagri number 20 of 2018 concerning management at every stage of the planning, implementation, administration, reporting and accountability. Several aspects of the planning, implementation, administration, reporting and accountability of finances are not yet appropriate due to inadequate human resources.